Examining the Relationship between Quality of Life and Baseline Hemoglobin Level in Lung Cancer with Chemotherapy Treatment Using EORTC QLQ-LC13 - Kole, Adelin; Suryanti Dwi Pratiwi; Ngakan Putu Parsama Putra; Ungky Agus Setyawan; Deden Permana (International Journal of Medical Science and Clinical Research Studies, 2024)
Background: The effect of lung cancer and its various treatments on the overall well-being can be substantial. This study seeks to examine the correlation between quality of life and baseline hemoglobin (Hb) levels in lung cancer patients who are receiving chemotherapy. Method: This study involved 30 patients with non-small cell lung cancer (NSCLC) who underwent platinum-based chemotherapy. Baseline Hb level were collected from medical records. The patients’ quality of life was assessed using interviews utilizing the EORTC QLQ-LC13 questionnaire. Result: Baseline Hb levels and pain relief after medication score was positively correlated (r=0.559, p=0.001). Baseline Hb levels and difficulty swallowing score was negatively correlated (r=-0.386, p=0.035). Determined cut-off point for the total score was 303.5. However, the correlation between Hb levels and overall quality of life was insignificant (r=-0.096, p=0.615). Conclusion: According to the quality of life indicators in the questionnaire, there is a notable association between lower baseline Hb levels and reduced effectiveness of pain relief medication, as well as an increase in difficulty swallowing. However, the underlying cause for this correlation is unclear. On the other hand, the correlation between baseline Hb levels and the overall scores of quality of life in the questionnaire was not found to be significant.